2019
DOI: 10.1016/j.meegid.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Geographical structure of bat SARS-related coronaviruses

Abstract: A B S T R A C TBats are the natural reservoirs of severe acute respiratory syndrome coronavirus (SARS-CoV) which caused the outbreak of human SARS in 2002-2003. We introduce the genetic diversity of SARS-related coronaviruses (SARSr-CoVs) discovered in bats and provide insights on the bat origin of human SARS. We also analyze the viral geographical structure that may improve our understanding of the evolution of bat SARSr-CoVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…MG772933) and only 79.5% genome sequence similarity to SARS-CoV. Phylogenetic analysis showed that the virus was clustered with SARS-CoV and bat SARSr-CoVs in subgenus Sarbecovirus Wei et al, 2020;Yu et al, 2019;Xu et al, 2020). Genomic analysis of 2019-nCoV and four typical coronaviruses (bat SARSr-CoV-Rp3, CoV-ZC45, CoV-ZXC21, and SARS-CoV-Tor2) showed a likelihood of recombination between 2019-nCoV and other coronaviruses among the subgenus .…”
mentioning
confidence: 99%
“…MG772933) and only 79.5% genome sequence similarity to SARS-CoV. Phylogenetic analysis showed that the virus was clustered with SARS-CoV and bat SARSr-CoVs in subgenus Sarbecovirus Wei et al, 2020;Yu et al, 2019;Xu et al, 2020). Genomic analysis of 2019-nCoV and four typical coronaviruses (bat SARSr-CoV-Rp3, CoV-ZC45, CoV-ZXC21, and SARS-CoV-Tor2) showed a likelihood of recombination between 2019-nCoV and other coronaviruses among the subgenus .…”
mentioning
confidence: 99%
“…We conducted a cross-sectional study in the districts of Yunnan, Guangxi, and Guangdong, China, which are known for their high levels of wildlife biodiversity, active wildlife trade activity, and historic zoonotic disease emergence events [3,5,10,14,22,24,27]. Eight study sites were selected in areas where we have previously reported diverse coronaviruses in bat populations [24] roosting close (within 5 km) to human dwellings.…”
Section: Study Location and Target Populationmentioning
confidence: 99%
“…In order for CoVs to recombine, they must first have the opportunity to do so by sharing overlapping geographic ranges, host species tropism, and cell and tissue tropism. Sarbecoviruses in bats tend to phylogenetically cluster according to the geographic region in which they were found [6,21]. Yu et.…”
Section: Introductionmentioning
confidence: 99%